DAMPAK PANDEMI TERHADAP PROFITABILITAS PERUSAHAAN INDUSTRI FARMASI - Ambardi aam juniawan; Adi Musharianto; Aam Aminah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
The purpose of this study is to analyze the differences in profitability of companies in the pharmaceutical sector before the pandemic and after the pandemic was announced by the government. This research is a descriptive and comparative study. Operationalization The variables used in this study are Gross profit margin or GPM, Net profit margin or NPM, Return on assets or ROA and Return on equity or ROE. The sampling technique used in this study was purposive sampling with a selected sample of 10 companies. With the criteria for pharmaceutical companies that have been listed on the IDX, pharmaceutical companies that publish annual financial reports for the 2019-2020 period. The data analysis technique used by the researcher is to use Descriptive Analysis, Normality Test (Shapiro Wilk) and Two-Mean Difference Test (Paired Sample T-Test). From the results of this study, it can be concluded that the profitability ratios measured by gross profit margin, net profit margin, return on assets and return on equity have no significant difference between before the pandemic and during the pandemic.Keywords : Profitability, pharmacy, pandemic